Analysis of the Impact of Environmental Law Awareness on Environmentally Unfriendly Behavior and Health Around Rivers Among Indonesian Millennials in the Context of Sustainable Development - Sembiring, Tamaulina Br.; Nasution, Emmi Rahmiwita; Wibisono, Okki Navarone; Wigati, RA. (Journal of Ecohumanism, 2025)
This study aims to analyze the impact of environmental legal awareness on environmentally unfriendly behaviors among Indonesian millennials living near urban rivers. Using the theoretical framework of legal enforcement, encompassing legal structure, legal substance, and legal culture, this research investigates the relationship between legal awareness and environmental behavior. A normative juridical method was employed, utilizing legislative and conceptual approaches. The findings reveal that environmental legal awareness significantly influences environmentally friendly behavior, with millennials exhibiting higher legal awareness demonstrating reduced pollution and improved public health outcomes. Furthermore, a positive correlation was identified between legal awareness and local initiatives in waste management along riverbanks. The study highlights the need for comprehensive legal education and the strengthening of law enforcement mechanisms to address environmental challenges more effectively. It also suggests that fostering a culture of legal compliance can contribute to long-term environmental sustainability. This research offers valuable insights into the role of legal awareness in fostering a more sustainable relationship between communities and their surrounding environment.